Global analysis of the controls on seawater dimethylsulfide spatial variability - Manville, George; Bell, Thomas G.; Mulcahy, Jane P.; Simó, Rafel; Galí, Martí; Mahajan, Anoop S.; Hulswar, Shrivardhan; Halloran, Paul R. (Biogeosciences, 2023)
16 pages, 5 figures, 1 table, supplement https://doi.org/10.5194/bg-20-1813-2023-supplement.-- Data availability: DMS and ancillary in situ data (SST and salinity) are sourced from the global surface seawater DMS database (GSSDD; https://saga.pmel.noaa.gov/dms/) and supplied by authors Rafel Simó, Martí Galí, Anoop S. Mahajan (Malaspina Expedition in 2010–2011, M10), Thomas G. Bell (North Atlantic Aerosol and Marine Ecosystem Study in 2015–2018, NAAMES; https://doi.org/10.5067/SeaBASS/NAAMES/DATA001, Behrenfeld et al., 2018), and George Manville (Southern oCean SeAsonaL Experiment in 2019, SCALE). Requests for access to M10 and SCALE DMS data can be sent to the corresponding authors (George Manville and Thomas G. Bell). Satellite data are available in online NASA repositories for chlorophyll a (https://doi.org/10.5067/AQUA/MODIS/L3M/CHL/2018, NASA Goddard Space Flight Center, 2018) and sea surface height anomalies (https://doi.org/10.5067/SLREF-CDRV2, Zlotnicki et al., 2019) Dimethylsulfide (DMS) emitted from the ocean makes a significant global contribution to natural marine aerosol and cloud condensation nuclei and, therefore, our planet's climate. Oceanic DMS concentrations show large spatiotemporal variability, but observations are sparse, so products describing global DMS distribution rely on interpolation or modelling. Understanding the mechanisms driving DMS variability, especially at local scales, is required to reduce uncertainty in large-scale DMS estimates. We present a study of mesoscale and submesoscale (< 100 km) seawater DMS variability that takes advantage of the recent expansion in high-frequency seawater DMS observations and uses all available data to investigate the typical distances over which DMS varies in all major ocean basins. These DMS spatial variability length scales (VLSs) are uncorrelated with DMS concentrations. The DMS concentrations and VLSs can therefore be used separately to help identify mechanisms underpinning DMS variability. When data are grouped by sampling campaigns, ...